PENELUSURAN BANJIR LEWAT PELIMPAH EMBUNG TB. SOSORNIAPOAN DIDESA LOBU TOLONG KECAMATAN PARANGINAN, KABUPATEN HUMBANG HASUNDUTAN PROVINSI SUMATERA UTARA - MANANDA TURE SIBURIAN (JURNAL ILMIAH KOHESI, 2020)
Lobu Tolong village, Paranginan Subdistrict, is one of the areas in Humbang Hasundutan Regency which is located in thehighlands. In this village area there is a small dam building and is called Embung Tambok Bolon (TB) Sosorniapoan. Byobserving the technical small dam layout, the reservoirs capacity of small dam can still be increased by increasing the heightof the small dam embankment. But socio-economically that is the inhabitants of the small dam management does not acceptthat the small dam embankment is elevated with the reason to avoid flooding and inundation in the yards, buildings andplants around the reservoir. In the downstream area of the TB. Sosorniapoan small dam there are rainfed rice fields and dryfields that are potential enough to be developed into agricultural areas with technical irrigation systems. In connection withthese conditions, studies were carried out so that flood discharge and flood height in the reservoir could be detected.From the results of the study it can be concluded, the calculation of flood discharge in the reservoir is 6.303 m3 / s and is atan elevation of + 1,400.70 m.